PENGARUH PERPUTARAN MODAL KERJA, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS (Studi Kasus Perusahaan Manufaktur Sub-Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019- 2021) - Kartikawati, Amelia Nur; Rizky Yuttama, Faizal; Alfizi, Alfizi (J-LEE - Journal of Law, English, and Economics, 2023)
Profitability is the ability of a company to make a profit. Profitability or profit is a goal for companies where companies try to achieve maximum profitability. This research is a quantitative research that aims to determine the effect of working capital turnover, leverage and company size on the profitability of food and beverage sub- sector manufacturing companies listed on the Stock Exchange during 2019-2021. The sampling technique uses the method purposive sampling with a total population of 30 companies and a sample of 11 companies. Data processing techniques using multiple linear regression analysis. Before carrying out the regression analysis, a classic assumption test was carried out which consisted of a normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results showed that the working capital turnover variable, leverage and firm size simultaneously have a positive and significant effect on profitability. turnover of working capital partially has a negative and significant effect on profitability leveraged, and firm size has a positive and significant effect on profitability. Keywords :Profitability,Working Capital Turnover,Leverage,Company Size